me ajudem por favor!!!
Anexos:
![](https://pt-static.z-dn.net/files/dab/7e3a26b227d97bc12e72f509fd160fb0.jpg)
Soluções para a tarefa
Respondido por
1
p = Rc1 + Rc2
p = raizq(48) + raizq(27)
raizq(48) = 4raizq(3)
raizq(27) = 3raizq(3)
entao
p = 4raizq(3) + 3raizq(3)
p= 7raizq(3)
p = raizq(48) + raizq(27)
raizq(48) = 4raizq(3)
raizq(27) = 3raizq(3)
entao
p = 4raizq(3) + 3raizq(3)
p= 7raizq(3)
amandaleslei:
obrigada! me ajudou muito!
Perguntas interessantes
Sociologia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Espanhol,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás